Analysis of the relevant factors for corneal graft rejection in the southern Liaoning region from 2019 to 2023 - Yan, Chunxiao; Zhang, Zhijian; Jin, Lin; Liu, Mengxin; Wang, Tianyi; Yang, Jinghao; Zhang, Lijun (Frontiers in Medicine, 2025)
BackgroundThe study aimed to review the etiology of corneal blindness and investigate the relative risk of corneal graft rejection (CGR) in the southern Liaoning region.MethodsThe clinical records of 359 patients (394 eyes) who underwent corneal transplantation at the Department of Keratoconus of the Third People’s Hospital of Dalian from January 2019 to December 2023 were retrospectively analyzed. The data included patients’ age, gender, occupation, diagnosis, surgical procedure, postoperative immune rejection, and neovascularization. The data were collected and descriptively analyzed to characterize the etiology of corneal blindness and to analyze the risk factors for postoperative immune rejection after corneal transplantation using logistic regression.ResultsThe mean age of the patients who underwent corneal transplantation was 55.90 ± 0.80 years, and there were more male patients than female patients with corneal blindness. Infectious keratitis (41.1%) was reported as the leading cause of corneal blindness, and penetrating corneal transplantation was the main surgical procedure for the recovery of sight. Preoperative corneal vascularization and penetrating corneal graft rejection were identified as risk factors for immune rejection of corneal grafts. The preoperative corneal vascularization was performed (p = 0.044, OR = 2.607). Penetrating keratoplasty (PKP) was performed (p = 0.024, OR = 1.953), and deep anterior lamellar keratoplasty was also performed (p = 0.801, OR = 1.088). Viral infections (p < 0.001, OR = 16.871) were the major risk factor for preoperative corneal neovascularization (CNV) compared to other etiologies, such as fungal infections (p < 0.001, OR = 0.018), mechanical ocular trauma (p < 0.001, OR = 0.034), immune keratitis (p = 0.023, OR = 0.152), and endothelial dysfunction (p < 0.001, OR = 0.054).ConclusionInfectious keratitis was identified as the major cause of corneal blindness in the southern Liaoning region over the past 5 years. Penetrating keratoplasty and preoperative corneal vascularization were the risk factors for corneal graft rejection. In addition, virus-derived keratitis was considered to be the main risk factor for corneal neovascularization, and deep anterior lamellar keratoplasty was not found to have an effect on corneal graft rejection in this study.